Antagonistic effect of Nigrospora oryzae against pathogenic fungi in dual culture assays - Sholihah, Mulianatus; Salsa Bella, Najwa; Dhiaulhaq, M. Rafi; Mustofa, Ali (Univeritas Papua, 2026)
This study aimed to evaluate the antagonistic activity of the endophytic fungus N. oryzae against four important plant pathogenic fungi, namely Fusarium solani, F. oxysporum, Alternaria alternata, and Acremonium kiliense, using in vitro dual culture assays. The antagonistic activity of N. oryzae was assessed using a dual culture method on Czapek Agar (CA) medium. Pure cultures were incubated at 25 °C for 72 h, after which 5-mm mycelial plugs were placed at a distance of 3 cm from the pathogenic fungi and incubated for an additional 72 h. Antagonistic activity was quantified by measuring colony radii (r₁ and r₂). Microscopic observations of the interaction zone were conducted using 1 × 1 cm² agar blocks stained with lactophenol cotton blue to identify antagonistic mechanisms. The results showed that N. oryzae inhibited the growth of all tested pathogens, with inhibition rates of 75.26% against A. alternata, 62.07% against A. kiliense, 43.63% against F. solani, and 33.26% against F. oxysporum. Macroscopic and microscopic observations indicated that the antagonistic interaction primarily involved competition for space and nutrients, as well as hyphal interactions resembling mycoparasitic behavior, including direct hyphal contact and hyphal coiling. These findings suggest that N. oryzae exhibits in vitro potential as a biological control agent against certain plant pathogenic fungi, particularly Alternaria and Acremonium. However, its antagonistic activity against Fusarium species was relatively lower, indicating that further studies are required to confirm the underlying mechanisms and to evaluate its effectiveness under more complex conditions.